A History of Magic and Experimental Science, Volume 2 (of 2) : During the First Thirteen Centuries of Our Era - Thorndike, Lynn, 1882-1965 (Salt Lake City, UT : Project Gutenberg, 2022)
"A History of Magic and Experimental Science, Volume 2" by Lynn Thorndike is a historical account written in the early 20th century. This volume explores the development of magic and experimental science during the twelfth and thirteenth centuries, featuring prominent figures and intellectual movements of the period. The book delves into the relationship between magic, natural sciences, and Christian thought, offering insights into how these subjects were intertwined during medieval times. At the start of this volume, Thorndike introduces key contributors to scholastic theology such as Peter Abelard and Hugh of St. Victor. He discusses the influence of these figures on magic and experimental science, emphasizing their significant roles in the growth of these disciplines. The opening chapter highlights Abelard's thoughts on astrology and the stars, demonstrating the complexities of medieval understanding of natural and supernatural forces. Through a detailed examination of these early scholars, the author sets the stage for a broader discussion on the evolution of thought in the realms of science and magic throughout the upcoming chapters. (This is an automatically generated summary.)
Release date is 2022-02-05
Tim Lindell, sf2001, and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive/American Libraries.)
Keywords: Science -- History; Magic -- History